Implementation of the Simple Additive Weighting (SAW) Method in a Decision Support System for Tourist Destination Selection in North Bali - Utama Giri, I Gede Andi; Dewa, Hari Putra Maha (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2023)
North Bali boasts remarkable natural and cultural attractions, but the process of choosing the best tourist spots is still based on personal opinions and lacks consistency. Without a fair and organized way to evaluate options, visitors and those involved often depend only on trends or individual tastes, which hinders effective promotion and handling of destinations. This research seeks to create a Decision Support System (DSS) that employs the Simple Additive Weighting (SAW) technique to fairly evaluate and rank travel sites using various factors like ease of access, appeal, amenities, hygiene, expenses, fame, security, and crowd levels. The suggested framework combines these prioritized elements to generate an overall rating for each potential location. By examining data from ten well-known spots in North Bali, Pura Ulun Danu Beratan topped the list with a score of (0.8800), showing excellence in most assessed aspects. The findings show that the SAW approach can reliably aid complex choices in tourism oversight, ensuring clear and dependable rankings. This tool offers a flexible and expandable structure suitable for evaluating tourism in other areas. Upcoming efforts will focus on adding live data feeds and visitor input via online or app interfaces to boost the system's precision and ease of use.